Management of Acute Renal Failure in Septicemic Neonates at a Tertiary Care Hospital - Sajan. T. Nair; Varun P G (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Neonatal septicemia or Sepsis neonatorum refers to systemic bacterial infection of infants during the first month of life. Infections are significant cause of mortality and long-term morbidity in neonates. The problem is that neonatal sepsis is a disease that may start with minimal or nonspecific symptoms and has a relatively low incidence, yet a high risk of mortality. Because the treatment is benign, relative to the disease and babies who develop sepsis often die rapidly, clinical practice has evolved such that many more babies are evaluated and treated for sepsis than have the condition, on the basis of subtle signs or risk factors, which resulted in over treatment. Subjects and Methods: This study was carried out in the neonatal intensive care units of the Pediatric Department of Medical College. The study includes the clinical profile of 100 cases of normal full-term neonates with septicemia admitted to the above centre during the period of study. Results: Most of the cases of acute renal failure required only conservative management (48.2%) whereas 11.1% of cases required peritoneal dialysis.Most of the cases of intrinsic renal failure (66.7%) required other modalities than conservative line in management, whereas most of the prerenal failure cases (60.0%) required only conservative management. All instances of peritoneal dialysis were in intrinsic renal failure group. Conclusion: Blood culture was the diagnostic criteria used for septicemia and the commonest organisms isolated were E. Coll, Klebsiella, Coagulase positive staphylococci and Group-B streptococci.